The Analytics of Additional Professional Education for Teachers in Pre-Professional Classes in Moscow Schools - E. Y. Petryaeva; N. S. Ageeva; Yu. I. Sumenkova; M. N. Fedorovskaya (Открытое образование (Москва), 2023)
Purpose of research. Teacher professional development (TPD) is a key issue of education policies globally. The solution of the issue is relevant for teachers of pre-professional classes in Moscow, since it is pre-professional classes that are assigned the role of effective tools for fulfilling the task of developing the innovative economy of the city.The objective of this study was to analyze the data on professional development and professional retraining of teachers in pre-professional classes in Moscow schools and find answers to the following questions:– What is the percentage of teachers engaged in additional professional education?– What is the intensity and dynamics of mastering programmes of additional professional education by teachers?– Where do teachers receive additional professional education?– Do the number of teachers in a school, the school’s ranking, the overall experience of teachers and the length of time of teachers in a given organization influence the additional professional education of teachers?Materials and methods. The study encompassed 2,215 teachers of pre-professional classes of 30 Moscow schools. The research methods included collection of data from the schools’ websites, processing data for statistical analysis, data analysis, and comparative analysis of different school indexes according to the selected parameters. Results. 72.8% of teachers of pre-professional classes were involved in professional development programmes, 21.8% of teachers – professional retraining programmes during the period of their work at school. 24% of teachers are continuously engaged in professional development. Mostly engaged in TPD are teachers who work at schools top-rated by “The Ranking of schools’ contribution to the quality education of Moscow students”. In addition, teachers with professional experience of less than 5 years are very actively engaged in teacher professional development. The number of school staff and prevalence of teachers with long record of service do not influence the scale of TPD engagement at schools. Additional professional education is not limited by the form of ownership, territorial affiliation, or the number of educational organizations in the region, and affects the positive dynamics in the diversification of teacher education, which is an important element of modern educational policy, the advantage of which is to improve the accessibility of education. The data of this research state that teachers were engaged in professional development programmes at 622 various organizations, of which 50.3% are state, and 49.7% - private organizations. Teachers were trained in 67 regions of Russia and 6 countries (the UK, the Netherlands, the Republic of Moldova, Switzerland, Ukraine, Estonia). The list of regions of the Russian Federation with the largest number of organizations in which teachers have mastered programs of additional professional education includes Moscow, the Moscow region, Saint Petersburg, Novosibirsk region, Krasnodar region, the Republic of Tatarstan, Stavropol region and the Udmurt Republic.Conclusion. The data obtained can contribute to the adoption of management decisions on the formation of professional development programs for teachers. The prospect of the study is the analysis of data on the impact of additional professional education of teachers on the educational results of students.